Peran Orang Tua Upaya Peningkatan Pembelajaran Anak Usia Dini Dengan Media Digital Interaktif - Nafa Riyona; Imelda Br Samosir; Dinda Aulia; M Aldri Hadianto; Siti Aisyah (LPPM STIKOM Tunas Bangsa, 2021)
This study investigates the role of parents in efforts to enhance early childhood learning using interactive digital media. This study aims to understand the extent to which parents' participation influences children's development in the digital era. Qualitative research methods were used to collect data through in-depth interviews with parents and observations of children's interactions with interactive digital media. The results highlight the importance of parents' role in directing children's digital media use, facilitating purposeful learning, and building a healthy relationship between children and technology. The findings provide insights into how parents can play a key role in supporting early childhood education through interactive digital media, thus making a positive contribution to early childhood learning in today's digital age.